New Digital Life for Fourteenth Century South Slavonic Scriptoria - Scarpa, Marco; Burlacu, Constanta; Paneva-Marinova, Desislava (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2021)
Written testimonies about the activity of South Slavic scribes and their monastic scriptoria in the 14th century are an essential resource of information, part of the world’s cultural and historical heritage which is at risk. Their tracking as well as the systematization and digitalization, will show how the information derived from medieval manuscripts is a source for the history of the Bulgarian state, but also for understanding the state policy in the fields of science and culture, and for constructing and managing new knowledge in today’s modern society. In this article we present the objectives of the Fourteenth Century South Slavonic Scribes and Scriptoria project. After giving a brief introduction to the cultural context of South Slavic lands in the 14th century, we proceed with describing how we intend to bring digital palaeography to the field of Slavonic Studies.